2017
DOI: 10.15406/apar.2017.06.00226
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Path Coefficient Studies of Yield and Yield Associated Traits in Bread Wheat (Triticum aestivum L.) Genotypes

Abstract: Sixty four wheat genotypes were tested in 8x8 simple lattice design at Ginchi, West Shewa in 2012/13 cropping season,. The overall objective was to assess the association among yield and yield contributing traits and identify traits those have the most direct and indirect effects on grain yield.. Analysis of variance revealed that there was a significant difference among the sixty four genotypes for all the characters studied. Grain yield had positive correlation with grain filling period, number of productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 4 publications
6
12
2
Order By: Relevance
“…Likewise, long flowering and maturing times negatively influenced grain yield. Similar results were found on wheat (Triticum aestivum) [49]. However, some findings showed that grain yield had highly significant positive correlation with maturity and flowering times in finger millet [50].…”
Section: Quantitative Traits Association and Partition Of Phenotypic Groups In Foniosupporting
confidence: 70%
“…Likewise, long flowering and maturing times negatively influenced grain yield. Similar results were found on wheat (Triticum aestivum) [49]. However, some findings showed that grain yield had highly significant positive correlation with maturity and flowering times in finger millet [50].…”
Section: Quantitative Traits Association and Partition Of Phenotypic Groups In Foniosupporting
confidence: 70%
“…The phenotypic correlation coefficients between the variables measured in the F 3 and F 4 generations are given in (2017) and Boussakouran et al (2021) pointed out that the best GY in semi-arid areas are the result of the genetic ability to produce more spikes per unit area associated with good spikes fertility. Slafer et al (2005) as well as Fellahi et al (2017) mentioned that the contribution to NS was more pronounced than that from NG which is formed in a more favorable period.…”
Section: Correlations Of the F 3 And F 4 Generation Traitsmentioning
confidence: 99%
“…In the present study, six variables including seed yield per plant, seed growth rate, days to seed fill, spikelets per spike, 1000-grain weight and days to flowering contributed above the expected average to the variability in PC1 and PC2 (table 3). Akram et al (2008), Mecha et al (2017) and Kumar et al (2020). https://doi.org/10.37992/2020.1102.063…”
Section: Resultsmentioning
confidence: 99%